FORMULASI DAN EVALUASI EMULGEL EKSTRAK ETANOL 96% DAUN CENGKEH (Syzygium aromaticum) DENGAN VARIASI KONSENTRASI EKSTRAK - Sasi Syabrina, Cinta; Intan Perma Sari, Rose; Danang Kurniawan, Tri; Mulia, Putri; Ikhsan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Clove leaves (Syzygium aromaticum) contain flavonoids and eugenol, which have the potential to act as natural antioxidants to protect the skin from free radical damage. This study aimed to formulate an ethanolic extract of clove leaves into a stable emulgel and determine the extract concentration that produces the best physical characteristics. The emulgel was chosen because it combines the advantages of an emulsion in delivering hydrophobic compounds with the comfort of gel application on the skin.The laboratory experimental study began with the preparation of clove leaf crude extract and extraction using a maceration method with 96% ethanol as a solvent. The resulting extracts were formulated into four formulas: F0 (base without extract), F1 (4%), F2 (8%), and F3 (12%), using Carbopol 940 as a gelling agent. Physical quality evaluation included organoleptic tests, homogeneity, pH, spreadability, viscosity, emulsion type, and hedonic tests.The results showed that all formulas were homogeneous and oil-in-water (O/W) emulsions. The pH value ranges from 5.00 to 5.93, matching the skin's pH. Spreadability ranges from 5.14 to 5.97 cm, and viscosity ranges from 5599.67 to 9080.33 cPs, meeting the requirements for topical formulations. Increasing the extract concentration affects the color, aroma, and reduces the viscosity of the formulation. Formulas F2 and F3 demonstrated the most optimal physical characteristics and spreadability.